ChemInform Abstract: Synthesis and Stereochemistry of New 1, 3‐Thiazolidine Systems Based on 2‐Amino‐2‐(mercaptomethyl)propane‐1, 3‐diol: 4, 4‐Bis(hydroxymethyl)‐1, 3‐thiazolidines and c‐5‐Hydroxymethyl‐3‐oxa‐7‐thia‐r‐1‐azabicyclo[3.3.0]octanes. Issue 17 (28th April 2014) - Morar, Cristina; Sacalis, Carmen; Lameiras, Pedro; Soran, Albert; Khartabil, Hassan; Antheaume, Cyril; Bratu, Ioan; Moldovan, Oana; Darabantu, Mircea
Abstract The new class of 2‐aryl‐4, 4, ‐bis(hydroxymethyl)‐1, 3‐thiazolidines (III) is investigated by NMR and IR spectroscopy and DFT calculations.